1993
DOI: 10.1111/j.1365-2249.1993.tb03457.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of tumour necrosis factor-alpha (TNF-α) and its receptors in normal and psoriatic skin: epidermal cells express the 55-kD but not the 75-kD TNF receptor

Abstract: SUMMARYThe distribution of TNF-a, p55 TNF reeeptor (TNF-R) and p75 TNF-R in normal skin and uninvolved and lesional skin from psoriasis patients has been investigated, using specific mono-and polyclonal antibodies. In normal skin, and uninvolved and lesional skin from psoriasis patients, p55 TNF-R is associated with epidermal keratinocytes and a network of upper dermal dendritic cells. This suggests that the actions oCTNF-a on epidermal ceNs/Hrn-o are mediated by binding to the p55 TNF-R. In Icsionat psoriasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 35 publications
5
83
1
1
Order By: Relevance
“…Although we did not address this issue, we do show that genetic ablation of TNFR1 is sufficient to partially protect mice from the full-blown skin inflammation upon IMQ treatment. Furthermore, we report specific upregulation of TNFR1 in the skin treated with IMQ, drawing another parallel to human psoriasis, in which TNFR1 expression is also increased (43,44). This finding shows another similarity between the IMQ-induced psoriasiform skin inflammation mouse model and human psoriasis.…”
Section: Discussionsupporting
confidence: 51%
“…Although we did not address this issue, we do show that genetic ablation of TNFR1 is sufficient to partially protect mice from the full-blown skin inflammation upon IMQ treatment. Furthermore, we report specific upregulation of TNFR1 in the skin treated with IMQ, drawing another parallel to human psoriasis, in which TNFR1 expression is also increased (43,44). This finding shows another similarity between the IMQ-induced psoriasiform skin inflammation mouse model and human psoriasis.…”
Section: Discussionsupporting
confidence: 51%
“…Generally, the response to TNF-α is triggered by binding to one of two distinct receptors, designated TNFR1 (55-kD TNFR) and TNFR2 (75-kD TNFR), which are differentially regulated in various cell types in normal and diseased tissue. In normal and psoriatic skin, epidermal cells express TNFR1 but not TNFR2 (25) and we also confirmed the TNFR1 expression in keratinocytes using quantitative RT-PCR (data not shown), indicating that the TNF-α-enhanced NGF secretion was mediated by TNFR1. However, there was no difference in TNFR1 mRNA expression levels between the TNF-α-treated and -untreated keratinocytes (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…TNF-α is a pivotal proinflammatory cytokine of the innate immune response and a key for skin inflammation (23). Plasma TNF-α concentration is increased in atopic dermatitis (24), and TNF-α and its receptors are upregulated in dermal blood vessels from patients with psoriasis (25). IFN-γ is also thought to be one of the important mediators in psoriatic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α, an autocrine stimulator as well as a potent inducer of other inflammatory cytokines, is produced by keratinocytes, epidermal Langerhans cells (LCs) and macrophages in the papillary dermis, 25) which has been considered a pivotal cytokine and a key mediator in inflammation in the skin. 26,27) In the present paper we further demonstrated that CA markedly inhibited TPA/A23187-induced TNF-α production in human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%